Musical Manipulations and the Emotionally Extended Mind - Krueger, Joel (Empirical Musicology Review, 2015)
I respond to Kersten’s criticism in his article “Music and Cognitive Extension” of my approach to the musically extended emotional mind in Krueger (2014). I specify how we manipulate—and in so doing, integrate with—music when, as active listeners, we become part of a musically extended cognitive system. I also indicate how Kersten’s account might be enriched by paying closer attention to the way that music functions as an environmental artifact for emotion regulation.